Acute basilar artery occlusion with recurrent shivering: A case report. Issue 39 (25th September 2020) - Lee, Chan-Hyuk; Jeon, Seung-Ho; Kim, Sang Yeon; Shin, Byoung-Soo; Kang, Hyun Goo
Abstract: Rationale: Shivering is an important physiological response of the body that causes muscle tremors to maintain temperature homeostasis. Traumatic brain injuries that affect the hypothalamus cause hypothermia, and physical removal of suprasellar tumors causes thermoregulation imbalance. However, no study has reported shivering due to ischemic stroke. Patient concerns: A 58-year-old male patient was admitted to our emergency department to evaluate severe stenosis of the basilar artery. While waiting for further examination, he exhibited coarse shivering and severe dysarthria. Diagnosis: Brain computed tomography angiography revealed occlusion of the entire basilar artery, and cerebral hypoperfusion was diagnosed in that area. Interventions: Transfemoral cerebral angiography (TFCA) was immediately performed, followed by thrombectomy of the basilar artery. Outcomes: Neurological deficits, including shivering, were rapidly reversed. The same symptom reoccurred 5 hours later, and TFCA was performed for thrombectomy and stenting, and neurological symptoms immediately reversed. The patient's neurological symptoms did not worsen during hospitalization. Lessons: Patients with acute basilar artery occlusion need prompt management because they have a higher mortality rate than those with other intracranial artery occlusions. When a patient exhibits neurological deficits accompanied by abrupt shivering for no specific reason, basilar artery occlusion must be considered.